NATURAL LIGHT INTENSITY AND VISUAL COMFORT THROUGH ADJUSTING THE HEIGHT OF THE CURTAIN OPENING: (Case: Room C.608-609, FTSP, Trisakti University, Jakarta) - Ghina Soraya; Popi Puspitasari; Khotijah Lahji (International Journal on Livable Space, 2022)
The type of activity, room area, and light intensity influence the visual comfort level of room users. In educational buildings, visual comfort influences the level of performance during the teaching and learning process of students. Students of the Bachelor of Architecture Study Program, FTSP, Trisakti University, use the Studio on the 6th floor (C.608-609) with 85% curtained glass window walls on the North and West, and 10% uncurtained bouvenlight windows on the South. It is estimated that the availability of natural light sources with such capacity is sufficient for the Studio learning process, but in fact users still turn on artificial lighting when working during the day. The hope is that by using curtained windows, students can regulate natural lighting needs to reduce the use of artificial lighting. Until this research was conducted, it was not known how high curtains met visual comfort standards. This research aims to create contour simulation of room’s natural light intensity C.608-609 using dialux kw06-288 software, in relation to adjust of curtains on windows with heights of 30 cm, 60 cm, 90 cm and 120 cm, and their impact on the user's feelings of visual comfort or discomfort. The results show that the distribution of natural light entering the room is not even and varied. According to SNI 03-6575-2001, the light intensity for a studio is 500-750 lux, but the measurement results show that at a curtain opening height of 120 cm, the light reach to the room with the furthest depth of 16.8m is not reached, so to achieve visual comfort the assistance of artificial lighting is needed, especially in the east-south of studio. Meanwhile, the area around the light source causes glare. Keywords: Light Intensity, Visual Comfort, Curtain Opening Height